Telemikst . Telemikst . Telemixt . Телемикст - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Work of the Commodity Exchange in Almaty; the transformation of Aeroflot into a public stock company; an interview with the CEO of a printing equipment company in Russia; equipment for food machinery in Nizhny Novgorod; an interview with Mary Intema on philanthropy in Russia. Featured in the program: Intema, Meri (Program Director for the Union of Independent States and Europe) Работа товарной биржи в Алма-Ате; преобразование Аэрофлота в акционерное общество; интервью с генеральным директором фирмы-поставщицы полиграфического оборудования в России; выставка-ярмарка оборудования для продовольственного машиностроения в Нижнем Новгороде; интервью с Мэри Интемой о благотворительной деятельности в России. В программе участвуют: Интема, Мэри (Директор программ СНГ и Европы)